Anglo-American Influence in Turkish Librarianship - Sekine Karakaş (Türk Kütüphaneciliği)
After the foundation of the Republic in our country, United States and Britain ıvere the most influential countries during the modernization stages of the librarianship. İn this article the opening of US1A and British Council libraries in Turkey are scruti- nized, as the first of a more conceptual research. United States and Britain are of the best countries that broaden the knowledge of the significance of the cultural relation- ship in a role towards an international programme in books and librarianship. These libraries, which quicked information about American and British cultural studies, presenting useful books and other tools to anyone interested in their contents seems to be an effective effort forming the library usage habit in our country.